Ground water Quality in Ubon- Ratchathani University Campus - Manl, Marina (Engineering and Applied Science Research, 2013)
Most of the water used at the Ubon-Ratchathani University (UBU) Campus is withdrawn from the shallow ground water at 4 - 6 meters depth from the surface. The analysis of ground water quality is, therefore, sIgnificant to the future use of water in the University The drinking water quality index setup by the Department of Mineral Resource adopted as a reference in this study The study results showed that the shallow ground water m the UBU Campus i!:i generally non saline, and can be considered as soft water. The quantity of tenus and manganise are higher than standards while the quantity of nitrate IS very low. However, the water turbidity i!:i qUIte hIgh as well as the level of septic contammatlOn As a whole the surface water reservoir at Nong-E-Jan1 is good enough to be the raw water for water supply sys tem in the UBU Campus.